Comparative Analysis of Bank Muamalat's Profitability in Implementing Fintech - Maulana, Zefri; Annisa Putri, Rifka; Sumarni, Mutia; Bin Mauluddin, Muhammad Ikhwan (Jurnal Ilmu Perbankan dan Keuangan Syariah, 2024)
Technological innovation has become the basis of information in the financial services industry, currently many new technologies are ready to drive the next wave of financial services innovation, one of which is financial industry innovation in the form of financial technology or fintech. The fintech industry emerged due to various constraints of banking and other financial institutions. The economic development of a country is strongly supported by the banking sector. The profitability of Bank Muamalat Indonesia is a benchmark in the banking world to determine the extent to which the bank has achieved its goal, namely obtaining good profits to increase bank profits. The aim of this research is to analyze the comparison of Bank Muamalat Indonesia before and after collaborating with fintech. The method used in this research is a quantitative method with the data source used from the annual financial report of Bank Muamalat Indonesia for the period 2006-2023. This research uses secondary data analysis using the normality test method, paired sample t-test for normally distributed data and the Wilcoxon signed test for data that is not normally distributed. The research results obtained show that at Bank Muamalat Indonesia the variables ROA, ROE, BOPO, GPM have a negative and significant effect after collaborating with fintech during the 2006-2023 period and the NIM and NPM variables have a positive and significant effect. This indicates that Bank Muamalat Indonesia's financial condition is experiencing income instability even though it has collaborated with fintech